(untitled) (Iranian Journal of Kidney Diseases, 2019)
Multicystic dysplastic kidney is a congenital kidney malformation consisting of multiple cysts of various sizes without a normal kidney morphology. Incontinentia pigmenti is a rare X-linked dominant genodermatosis, which is usually lethal in males, that presents clinically in 4 stages. Here, we report a case of multicystic dysplastic kidney with ureterovesical junction obstruction and incontinentia pigmenti. Coexistence of these two rare diseases may be a coincidental phenomenon or an association between the two may exist.